1998
DOI: 10.1093/emboj/17.10.2736
|View full text |Cite
|
Sign up to set email alerts
|

p53-inducible human homologue of Drosophila seven in absentia (Siah) inhibits cell growth: suppression by BAG-1

Abstract: The Drosophila seven in absentia (sina) gene is required for R7 photoreceptor cell formation during Drosophila eye development, where it functions within the Ras/Raf pathway and targets other proteins for degradation via associations with a ubiquitinconjugating enzyme. Recently, a mammalian sina homologue was reported to be a p53-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
166
1
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(177 citation statements)
references
References 57 publications
(94 reference statements)
9
166
1
1
Order By: Relevance
“…Using epitope-tagged protein, cellular localization of SIAH-1 was reported as predominantly cytoplasmic (Hu et al, 1997) or nucleic (Matsuzawa et al, 1998). It was also shown that the ring domain of the protein was required for the formation of punctuated structures in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using epitope-tagged protein, cellular localization of SIAH-1 was reported as predominantly cytoplasmic (Hu et al, 1997) or nucleic (Matsuzawa et al, 1998). It was also shown that the ring domain of the protein was required for the formation of punctuated structures in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…SIAH-1 binds Bag-1 protein and inhibits cell growth (Matsuzawa et al, 1998). Bag-1 is a widely expressed protein with an ubiquitin-like domain that binds and cooperates with Bcl-2 in suppressing cell death.…”
Section: Introductionmentioning
confidence: 99%
“…[60][61][62][63][64][65][66][67][68][69] The functional diversity of BAG domain proteins is paralleled by an abundance of genes of this family throughout evolution, with homologs identified in a variety of organisms, including yeast, worm, invertebrates, amphibians, mammals, and plants. 21,59,60,70 Database searches indicate the presence of eight genes that encode proteins with the BAG domain in Arabidopsis thaliana.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, p53-induced SIAH expression may participate in the phosphorylation-independent degradation of bcatenin; however, its relevance in HCCs has not been shown until now (Matsuzawa et al, 1998;Liu et al, 2001a;Matsuzawa and Reed, 2001). Secondly, accumulation of b-catenin wt correlates positively with a high exposure of aflatoxin B1 (Devereux et al, 2001) and with mutational inactivation of p53 in HCCs (Cagatay and Ozturk, 2002); however, a direct connection between all three parameters (aflatoxin intoxication, aflatoxin-specific G/T mutation in p53 mut/249 and bcatenin enrichment) has not been shown so far.…”
Section: Cross-talk With Protumorigenic Factorsmentioning
confidence: 99%